Prediction of depth from skin to subarachnoid space based on preoperative anthropometric assessment: an observational study - Mamta Khandelwal; Ekta Tiwari; Priyanka Jain; Chitra Singh; Nachiketa Bharadwaj; Darshan N (Journal of Applied Pharmaceutical Research, 2023)
Background and aim: An accurate placement of spinal needle is crucial while injecting drugs to avoid a failed sub arachnoid block (SAB). A pre puncture estimation of skin to subarachnoid depth (SSD) may guide accurate spinal needle placement. This study is aimed to predict the depth from skin to subarachnoid space based on pre-operative anthropometric assessment and to find out formula for predicting SSD, best suited in terms of accuracy when compared with observed depth. Method: In this hospital based, prospective, observational study, a total of 120 patients, of which 68 were men, and 52 were women (non-pregnant) with a mean age of 59.75 ±14.1 kilograms. The SSD was measured after SAB was performed. This SSD was compared with the predicted SSD calculated using the Abe’s, Bonadio’s, Craig’s, Stocker’s, and Chong’s modified formulae. Analysis was done using unpaired t test for quantitative data to determine best suited formula to predict SSD in our population in terms of both accuracy and ease of application. Pearson correlation test was also done. Results: The observed SSD in the overall study population was 4.96 ± 0.67 cm. Stocker’s formula is closest with a mean difference of 0.17cm. In males the mean observed depth was (5.06±0.60 cm) more than that in the non-pregnant female population (4.83±0.74cm). These anthropometric variables were statistically significant with a presentation value of <0.001. Conclusion: Among various formulae Stocker’s formula can most accurately predict the SSD when applied to Indian population.